ETIOLOGICAL FACTORS AND INFERTILITY TREATMENT TACTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article under discussion discusses etiological factors infertility treatment tactics. The authors of the article consider that infertility affects millions of people of reproductive age worldwide and affects their families and communities. Infertility treatment includes prevention, diagnosis and treatment of infertility. Environmental and lifestyle factors such as smoking, excessive alcohol consumption and obesity can have an impact on fertility. Treatment of infertility usually starts with general health measures, including diet, avoiding bad habits, reducing body weight and avoiding factors that may reduce fertility. If hormonal abnormalities or inflammatory processes are detected, medication therapy is prescribed at the same time.